PROMOTION OF FOREIGN TRADE IN THE COUNTRY'S ECONOMY - B. Z. Arzimatov (American Journals, 2023)
In this article, the issues of encouraging the country's export policy, strengthening foreign trade relations with foreign countries and eliminating some obstacles, ways to increase the country's export potential, and several proposals are put forward.
Keywords: Trade, export, investment, concession, tax, enterprise, excise, realization, commodity, logistics, insurance, incentive, compensation, market.